2013
DOI: 10.1177/1524839913485242
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Tobacco-Related Disparities Among Pacific Islanders Through Leadership and Capacity Building

Abstract: Tobacco remains a major risk factor for premature death and ill health among Pacific Islanders, and tobacco-related disparities persist. Eliminating these disparities requires a comprehensive approach to transform community norms about tobacco use through policy change, as contained in the World Health Organization (WHO) international Framework Convention on Tobacco Control (FCTC). Three of the six US-affiliated Pacific Islands – the Federated States of Micronesia (FSM), Palau and the Marshall Islands – are Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…New Caledonia, Wallis and Futuna, and French Polynesia are also not signatories. Although some of these PICTs are nevertheless active in tobacco control, exclusion from the FCTC creates inequalities within the Pacific and necessitates reliance on voluntary implementation of the treaty’s provisions ( 25 ).…”
Section: Implications For Policymentioning
confidence: 99%
See 1 more Smart Citation
“…New Caledonia, Wallis and Futuna, and French Polynesia are also not signatories. Although some of these PICTs are nevertheless active in tobacco control, exclusion from the FCTC creates inequalities within the Pacific and necessitates reliance on voluntary implementation of the treaty’s provisions ( 25 ).…”
Section: Implications For Policymentioning
confidence: 99%
“…Initiatives can build on factors known to further tobacco control in the Pacific. These include strong political, government, and community leadership to drive the agenda and partnerships such as Pacific Partners for Tobacco Free Islands ( 25 ). Capacity building and engagement with local champions, traditional leaders, faith-based organizations, and antitobacco advocacy organizations are essential to implementing effective policies ( 21 , 25 , 27 ).…”
Section: Implications For Policymentioning
confidence: 99%
“…Although one outreach study suggests that Asian grocery stores are an appropriate venue for outreach about smoking-cessation resources and a Street Team approach is impactful, 12 future outreach for Medi-Cal enrollees might consider more targeted messaging for smokers, or partner with efforts to enroll the public in Medi-Cal. Outreach to PIs, who have smoking prevalence rates higher than the general population, 22 needs to be timed with large community festivals for higher impact, a common outlet for reaching communities for health promotion. 22 Limitations Previous research has found a significantly greater proportion of nonsmoking family and friends calling on behalf of smokers (termed proxy) on the Asian-language lines compared with the English-language quitline in California, 23 but this study only includes Medi-Cal smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Outreach to PIs, who have smoking prevalence rates higher than the general population, 22 needs to be timed with large community festivals for higher impact, a common outlet for reaching communities for health promotion. 22 Limitations Previous research has found a significantly greater proportion of nonsmoking family and friends calling on behalf of smokers (termed proxy) on the Asian-language lines compared with the English-language quitline in California, 23 but this study only includes Medi-Cal smokers. Other outreach promoting free nicotine patches for callers to the Asian Smokers' Quitline cooccurred during the MIQS program-a Centers for Disease Control and Prevention−funded nationwide campaign and a countywide campaign funded by Los Angeles County's Community Transformation Grant.…”
Section: Discussionmentioning
confidence: 99%
“…Another parent leader said, "Grew confidence by speak up, stand-up, voice out." Previous researchers found in their work among Pacific Islanders that investment in leadership development led to effective leaders and champions that ensured adoption of interventions (David et al, 2013). Community and academic partners found overall that the length of time for the workshops were necessary and protective for leadership and research capacity building.…”
Section: Initially Shy and Humble And Through Participation Transformmentioning
confidence: 99%